Age differences in PTSD among Canadian veterans: age and health as predictors of PTSD severity. (9th September 2014) - Konnert, Candace; Wong, May
ABSTRACT: Background: To date, few studies have investigated age differences in posttraumatic stress disorder (PTSD) symptoms and none has examined age differences across symptom clusters: avoidance, re-experiencing, and hyperarousal. The first objective of this study was to investigate age differences in PTSD and its three symptom clusters. The second objective was to examine age and indices of health as predictors of PTSD symptom severity. Methods: Participants were 104 male veterans, aged 22 to 87 years, receiving specialized mental health outpatient services. Assessments included measures of health-related quality of life, pain severity, number of chronic health conditions, and symptoms of PTSD, both in total and on the symptom clusters. Results: There were significant age differences across age groups, with older veterans consistently reporting lower PTSD symptom severity, both in total and on each of the symptom clusters. Hierarchical regression analyses indicated that the inclusion of health indices accounted for significantly more variance in PTSD symptoms over and above that accounted for by age alone. Pain severity was a significant predictor of PTSD total and the three symptom clusters. Conclusions : This is the first study to report lower levels of PTSD severity among older veterans across symptom clusters. These findings are discussed in relation to age differences in the experiencing and processing of emotion, autobiographical memory, and combat experiences. This study also emphasizes the importance of assessing pain in those with symptoms of PTSD, particularly older veterans who are less likely to receive specialized mental healthcare.